Online Learning: Leading e-Learning at Higher Education - Mutiara Ayu (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2020)
In the 'Information Age' where the demand of knowledge raises, the students are expected to retrieve more information to support and develop their learning process. Some universities have progressively opened up to the opportunity of e-learning concept, and they are currently integrating e-learning in their teaching to accommodate the diverse need in learning and providing more interactive materials that allow easy access to information. E-learning has the potential to transform the way of teaching and studying across the board. It can develop standards, and improve involvement in learning. This cannot substitute teachers or lecturers role, but in addition to existing methods it can develop the quality and decrease the time spent. This paper aims at presenting an overview of the extent to which e-learning is used at higher education and explores e-learning from the perspective of students and teachers. It also briefly explains the current condition of e-learning that utilizes interactive technology to enhance the learning experience.Keywords: e-learning, higher education, technology